ONLINE COURSE REGISTRATION APPLICATION AT EDEN EVERYDAY ENGLISH BOGOR - Dinda Ayu Muthia; Yetrivo Efendy (Jurnal Teknoinfo, 2021)
The course is one of the education provided outside formal (non-formal) schools to develop personal abilities and skills. Eden Everyday English Course Institute is an Institution located in Bogor. In this institution, the registration process for students is done manually by filling in the registration form provided by the admin. Eden Everyday English Course Institute is one of the courses where the number of applicants increases every year, this causes the administration department cannot manage everything properly and feels overwhelmed so that it is not effective. With the increase in the number of students registering each year, it would be better if a web-based registration system was created, so that it could simultaneously serve as a medium for promoting the course institution. The purpose of this research is to create a web-based application to help the process of registration for new students in Eden Everyday English Course Institute using the waterfall method. Many studies, especially in the field of information system development, use the Waterfall method. This online course registration application is effective and efficient because it is supported by an integrated system. This application improves the quality of information and the efficiency of the implementation of online course registration.